Przedstawienie Litanii Loretańskiej w ołtarzu Najświętszej Marii Panny z klasztoru Reformatów w Poznaniu - Sulewska, Renata (TECHNE. Seria Nowa, 2018)
Following the 1758 replacement of the altarpieces in the church of the Franciscans of Primitive Observance in Poznań, one more retable was made in 1763, this time for the monastery. It was placed in the ‘lower cloister’, next to the entrance to the refectory. The retabulum intended for the monastery has not survived and is known only from a description included in The Chronicle of the Franciscans of Primitive Observance in Poznań (Kronica Reformatow poznańskich). The altarpiece was dedicated to the Blessed Virgin Mary, and its imagery encompassed the symbols that presented invocations from the Litany of Loreto, commencing with the Kyrie eleison, to the Lamb of God. Presumably, the set of symbols in the Poznań retable, which corresponded to individual invocations, was not based on a single source. Even if it were possible to determine one such source, however, the altarpiece was significantly modified by the introduction of symbols of a ‘local’ origin, such as the representation of the Polish eagle with a crown in his beak, referring to the invocation Regina Regni Poloniae, or the image of a woodworking plane and a bell that symbolized invocation Mother most admirable. This last image referred back to events that had taken place in the Poznań monastery and could not have been correctly interpreted without information contained in The Chronicle. Symbols and emblems recorded in the text offer a point of departure for reconstructing the Poznań retabulum. In general, these retables can be divided into two major types. The first one has an architectonic organization enriched with sculpted symbols or cartouches with relief designs applied to the frame or supported by sculpted figures placed in the structure. The second type is represented by non-architectonic retables where imagery is incorporated into an ornamental frame. As can be inferred from the description in The Chronicle, the altar dedicated to the BVM within the Franciscan monastery belonged to the former type. This description also makes it possible to reconstruct the retable – an aedicula with towering structures on both sides and an elaborate crowning section. All its elements – the structure and the complementing representations – had a symbolic meaning. Given the complexity of applied solutions (imposed by its content and symbolism) and its elaborate form, the Poznań altar dedicated to the BVM differed from other retables that were constructed in Franciscan churches in the territories of Greater Poland in the second half of the 18th century, most of them modelled on the retables in the Franciscan church in Boćki.